Exfoliative esophagitis secondary to tislelizumab: a case report - Wang, Mingxing; Sun, Qingming; Dong, Wanhui (Frontiers in Oncology, 2024)
Tislelizumab, as a PD-1 inhibitor, has demonstrated significant efficacy in cancer treatment. However, it may also induce immune-related adverse events (irAEs). This case report describes a patient who developed oral ulcers and dysphagia following treatment with tislelizumab, which was diagnosed as exfoliative esophagitis through endoscopic examination. The condition improved after corticosteroid pulse therapy. A review of the relevant literature revealed no prior reports of immune checkpoint inhibitor (ICI)-related esophagitis cases, prompting an exploration of the potential pathophysiological mechanisms and therapeutic strategies. This report emphasizes the importance of vigilance for rare irAEs during ICI therapy, advocating for early detection and timely intervention.